2013
DOI: 10.1021/ja4042675
|View full text |Cite
|
Sign up to set email alerts
|

How Light-Harvesting Semiconductors Can Alter the Bias of Reversible Electrocatalysts in Favor of H2 Production and CO2 Reduction

Abstract: The most efficient catalysts for solar fuel production should operate close to reversible potentials, yet possess a bias for the fuel-forming direction. Protein film electrochemical studies of Ni-containing carbon monoxide dehydrogenase and [NiFeSe]-hydrogenase, each a reversible electrocatalyst, show that the electronic state of the electrode strongly biases the direction of electrocatalysis of CO2/CO and H+/H2 interconversions. Attached to graphite electrodes, these enzymes show high activities for both oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 32 publications
6
57
0
4
Order By: Relevance
“…On TiO 2 , CdS, and NiO, the naturally intense electrocatalytic activity is controlled instead by the properties of the electrode material [60 ,67 ,68 ], specifically the availability of the majority carriers. The reduction potentials of the H + /H 2 and CO 2 /CO couples lie close (within k B T) to the flatband potentials E fb of the n-type materials TiO 2 and CdS: as a result, the normally reversible electrocatalytic activity of CODH and [NiFeSe]-H2ase is rectified because the n-type materials become increasingly insulating as the potential is raised through and above E fb [67 ]. In contrast, when attached to p-type NiO, CODH behaves as a unidirectional CO oxidiser in the dark: holes are the majority carriers and the depletion layer prevents electrocatalytic CO 2 reduction [60 ].…”
Section: Perspectives and Insightsmentioning
confidence: 57%
“…On TiO 2 , CdS, and NiO, the naturally intense electrocatalytic activity is controlled instead by the properties of the electrode material [60 ,67 ,68 ], specifically the availability of the majority carriers. The reduction potentials of the H + /H 2 and CO 2 /CO couples lie close (within k B T) to the flatband potentials E fb of the n-type materials TiO 2 and CdS: as a result, the normally reversible electrocatalytic activity of CODH and [NiFeSe]-H2ase is rectified because the n-type materials become increasingly insulating as the potential is raised through and above E fb [67 ]. In contrast, when attached to p-type NiO, CODH behaves as a unidirectional CO oxidiser in the dark: holes are the majority carriers and the depletion layer prevents electrocatalytic CO 2 reduction [60 ].…”
Section: Perspectives and Insightsmentioning
confidence: 57%
“…Recently, Armstrong's group have exploited highly active carbon monoxide dehydrogenase (CODH) to serve as the co-catalyst for PEC CO 2 reduction [32,164]. For instance, a CODH-form carboxydothermus hydrogenoformans was employed to functionalize a dye-sensitized p-NiO photocathode, which could selectively reduce CO 2 to CO under visible-light illumination with good stability (Fig.…”
Section: Enzymatic Biocatalystsmentioning
confidence: 99%
“…Of the semiconductor materials that they investigated, photocatalysts prepared with Evonik Degussa P25 TiO2 (a commercially available 3:1 mixture of anatase/rutile) and ordinary anatase TiO2 nanoparticles were found to be the most effective, in terms of overall turnover rate. More recently, Bachmeier et al [23] demonstrated that semiconducting electrodes can be used to impose directionality on reversible catalysts operating in the region of the flatband potential. Although these enzymes are unsuited for long-term, large-scale systems, their results provide valuable insight for developing integrated artificial systems (based ultimately on abundant chemical catalysts) [23].…”
Section: Conversion Of Co2 To Carbon Monoxidementioning
confidence: 99%
“…The reaction rate can be increased More recently, Bachmeier et al [23] demonstrated that semiconducting electrodes can be used to impose directionality on reversible catalysts operating in the region of the flatband potential. Although these enzymes are unsuited for long-term, large-scale systems, their results provide valuable insight for developing integrated artificial systems (based ultimately on abundant chemical catalysts) [23].…”
Section: Conversion Of Co2 To Formic Acid/formatementioning
confidence: 99%